Термин «цай» (才) в концепции морального совершенствования в трактате «Мэн-цзы» - ГОРДИЕНКО, Андрей Витальевич (Гуманитарные исследования в Восточной Сибири и на Дальнем Востоке, 2025)
The article attempts to clarify the meaning of the term «cai» (才) in the concept of moral improvement in Mengzi by analyzing the cases of its use in the context of statements related to this topic. The author concludes that cai, that marks a special (remarkable and transitory) character of a certain property, within this concept denotes the physical characteristic that enables xin (heart-mind) to initiate moral behaviour regardless of circumstances.